HUBUNGAN PENDIDIKAN KESEHATAN TENTANG KPSP DENGAN PENGETAHUAN GURU KB TK TENTANG KPSP - Nurun Nikmah; Lidia Aditama Putri; Novi Anggraeni; Rizqy Aulia Savitri; Rina Arfandiyah (LPPMK STIKES Widyagama Husada, 2021)
The KPSP (Pre-Development Screening Questionnaire) examination which is carried out for early detection of growth and development of children aged 0-72 months is actually not only the task of health workers, but also people who often interact with children, one of which is Playgroup and Kindergarten teachers. But unfortunately, it’s very rare for these playgroup and kindergarten teachers to understand and carry out KPSP examinations for their students. This study aims to analyze the relationship of health education about KPSP with the knowledge of playgroup and kindergarten teachers about KPSP. It was pre-post test design, the sample werw taken randomly by simple random sampling on 33 playgroup and kindergarten teachers at Permata Hati Bangkalan and Taman Posyandu Eforbia Bangkalan. The data were analyzed using paired T-test with a significance of =0.05 using SPSS. The results showed that there was a relationship between health education about KPSP with the knowledge of Plygroup and Kindergarten teachers about KPSP (p value < 0.001). The average value of teachers knowledge about KPSP has increased before and after health education, from 49.39 to 62.88. It can be concluded that educational activities through health education are effective in increasing the knowledge of Playgroup and Kindergarten teachers about KPSP.